2018
DOI: 10.1007/s11356-018-1259-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and utilization of temple waste flowers in Coimbatore District

Abstract: The present work deals with collection, handling, utilization, and management of the waste flowers that are coming out of the temples in Coimbatore District, Tamilnadu, India. An attempt has been made to provide a current situation and complete analysis of temple waste flowers (TWFs) with suggestions and recommendations. As a part of Clean India, Clean and Green Kovai (Green Coimbatore) mission, this paper gives an idea to reduce the volume of temple waste flowers by converting into activated carbon by direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Mass percentage of moisture content, ash content and volatile content, fixed carbon, bulk density (g/cm 3 ), porosity percentage and specific gravity of all CFS were determined according to standard procedures [26]. The surface morphology and elemental compositions of RP, WCP, YCP, MGP, TRP and TP have been characterized using SEM and EDS.…”
Section: Analysis Of Crushed Flower Samples (Cfs)mentioning
confidence: 99%
“…Mass percentage of moisture content, ash content and volatile content, fixed carbon, bulk density (g/cm 3 ), porosity percentage and specific gravity of all CFS were determined according to standard procedures [26]. The surface morphology and elemental compositions of RP, WCP, YCP, MGP, TRP and TP have been characterized using SEM and EDS.…”
Section: Analysis Of Crushed Flower Samples (Cfs)mentioning
confidence: 99%
“…Figure 6 illustrates the effect of dyebath pH (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) on K/S values of the dyed fabrics. It is observed that the optimum K/S is obtained at acidic pH of 4.…”
Section: Effect Of Ph In Dyeing Processmentioning
confidence: 99%
“…However, sometimes it is found that the temple waste is discarded into the rivers or dumped in an open place. The improper disposal of such waste creates an array of environmental and human health problems [2,3]. According to the WHO, 36% of the chemicals used in flower farms are extremely toxic, and when discarded in landfills, they can produce 22 times more environmentally destructive greenhouse gases than carbon dioxide [4].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of flower waste generated vary from place to place like in Dargahs the flower waste mostly consists of jasmine flowers, in Gurudwaras mainly marigold flowers are used and in case of temples marigold, lotus, rose, etc. (Elango and Govindasamy, 2018). Flower wastes are composed of high lignocellulose, cellulose, crude proteins, crude fibers, essential oils, nitrogen-bearing compounds, etc.…”
Section: Composition Of Flower Wastesmentioning
confidence: 99%
“…Some flowers can also be used as veterinary feed. Nowadays activated carbon is being prepared from temple flower waste which has a wide range of utility due to its adsorption properties (Elango and Govindasamy, 2018).…”
Section: Miscellaneous Usesmentioning
confidence: 99%